Influence of selected soil parameters on amino acid profile in Stellaria media - M. Dziągwa-Becker, Magdalena; Kalitowska, Olga; A. Oleszek, Wiesław (Polish Journal of Agronomy, 2016)
The study investigates the relationship between soils that vary for different basic physicochemical parameters (pH, phosphorus and potassium content, granulometric composition and soil organic matter content) and the free amino acids con- tent of Stellaria media. According to some research, plant amino acid profile is a good indicator of the condition of the soils on which plants are grown. In this experiment, a rapid and sensitive liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) method was used for the identification and quanti- fication of nineteen proteinogenic amino acids in Stellaria media samples, which is a very common weed found worldwide. Signif- icant linkage was found between the soil parameters and Stellaria media amino acid content. Garden soil is the most favourable soil for amino acid content. Glutamine, glutamic and aspartic acid are the most abundant amino acids in Stellaria media grown on all three tested soils.